Pan-African Banks : Opportunities and Challenges for Cross-Border Oversight. (Policy Papers; Policy Paper ;, 2014)
There has been a rapid expansion of pan-African banks (PABs) in recent years, with seven major PABs having a presence in at least ten African countries: three of these are headquartered in Morocco, two in Togo, and one each in Nigeria and South Africa. Additional banks, primarily from Kenya, Nigeria, and South Africa, have a regional presence with operations in at least five countries. PABs have a systemic presence in around 36 countries. Overall, the PABs are now much more important in Africa than the long-established European and American banks.